Hubungan Pengetahuan Ibu Hamil tentang Tanda Bahaya Kehamilan dalam Pemanfaatan Buku KIA di Puskesmas UPTD Puskesmas Karanganyar, Semarang - Fitri Rochmawati; Noveri Aisyaroh; Muliatul Jannah (Jurnal Kebidanan Harapan Ibu Pekalongan, 2026)
Signs of pregnancy complications are important information for every pregnant woman in order to prevent complications that can increase maternal morbidity and mortality rates. The Maternal and Child Health (MCH) Handbook contains this information, but its use in the community is still not optimal. This study aims to determine the relationship between pregnant women's knowledge of pregnancy complications and their use of the MCH Handbook. This study used a quantitative method with a cross-sectional design. The number of respondents was 53 pregnant women selected using the Slovin formula. Data were collected through a questionnaire containing 20 items. Data analysis used univariate and bivariate analysis (Chi-Square test). The results showed that most respondents were aged 20–35 years (79.25%), were in their third trimester (52.83%), and were multigravida (56.60%). Most respondents had good knowledge of the danger signs of pregnancy (77.36%) and high utilization of the KIA Book (86.79%). The Chi-Square test produced a p-value of 0.000 (<0.05), indicating a significant relationship between the knowledge of pregnant women and the utilization of the KIA Book. Overall, good knowledge contributes to increased utilization of the KIA Book as a source of information and an early detection tool for maternal health.